The grandiculus- and metacarpalis-group of the genus Apanteles Foerster, 1862 (Hymenoptera, Braconidae, Microgastrinae) from China, with descriptions of eight new species - Liu, Zhen; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2014)
Two species groups (the grandiculus- and the metacarpalis-group) of genus Apanteles Foerster (Hymenoptera, Braconidae, Microgastrinae) from China are revised and keyed, with eight new species, namely, A. muticiculus Liu & Chen, sp. n., A. parvus Liu & Chen, sp. n. and A. flavicapus Liu & Chen, sp. n. of the grandiculus-group; A. transtergum Liu & Chen, sp. n., A. malleus Liu & Chen, sp. n., A. dumosus Liu & Chen, sp. n. A. cosmopterygivorus Liu & Chen, sp. n. and A. incurvus Liu & Chen, sp. n. of the metacarpalis-group, and two newly recorded species of the metacarpalis-group described and illustrated. Keys to the Chinese species of these two species-groups are provided.